Self-reported symptoms of pain and depression in primary fibromyalgia syndrome and rheumatoid arthritis. (1st February 2014) - Scheidt, Carl Eduard; Mueller-Becsangèle, Juliane; Hiller, Kristina; Hartmann, Armin; Goldacker, Sigune; Vaith, Peter; Waller, Elisabeth; Lacour, Michael
Abstract: Background: Primary fibromyalgia syndrome (FMS) is associated with substantial psychiatric comorbidity. The aim of the present study was to investigate the interrelationship between self-reported symptoms of depression and pain in FMS compared with rheumatoid arthritis (RA). Methods: In a cross-sectional study, 100 patients with FMS and 50 patients with RA were compared with regard to depression and psychopathology using the Symptom Check List (SCL-27). Group comparisons were calculated by parametric and non-parametric tests. The association between pain intensity and depression was determined by correlation analyses and multivariate statistical procedures (CATREG). Results: Pain intensity was significantly higher in FMS compared with RA. FMS patients also scored significantly higher on all subscales of the SCL-27 including the depression scale and the General Symptom Index (GSI) ( P < 0.001). These group differences remained stable even after correcting for pain intensity. Correlation analyses revealed an association between pain intensity and depression in FMS but not in RA ( R = 0.419, P < 0.001). Conclusion: FMS patients in tertiary referral centers suffer from higher levels of pain intensity than RA patients. Depression predicts levels of pain in FMS but not in RA and is therefore an important target of intervention.